2014
DOI: 10.1002/ajmg.b.32237
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan for cognitive trait loci of dyslexia: Rapid naming and rapid switching of letters, numbers, and colors

Abstract: Dyslexia, or specific reading disability, is a common developmental disorder that affects 5–12% of school-aged children. Dyslexia and its component phenotypes, assessed categorically or quantitatively, have complex genetic bases. The ability to rapidly name letters, numbers, and colors from rows presented visually correlates strongly with reading in multiple languages and is a valid predictor of reading and spelling impairment. Performance on measures of rapid naming and switching, RAN and RAS, is stable throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Some part of this stability can be explained by genetic sources, as a strong genetic influence has been shown in RAN performance (e.g., Byrne et al, 2006;Christopher et al, 2015;Davis et al, 2001;Petrill, Deater-Deckard, Thompson, DeThorne, & Schatschneider, 2006;Petrill et al, 2010;Samuelsson et al, 2007). There is also recent research evidence for specific genes that have been associated with RAN performance (Naples, Chang, Katz, & Grigorenko, 2009), some of them the same as those previously associated with dyslexia (Rubenstein, Raskind, Berninger, Matsushita, & Wijsman, 2014). In addition, brain imaging studies have recently shed further light on the neural basis of RAN performance, showing that activation during naming tasks is present in the areas involved in attention, and that eye-movement control is also present in the areas usually associated with reading tasks (McCrory, Mechelli, Frith, & Price, 2005;Misra, Katzir, Wolf, & Poldrack, 2004).…”
Section: What Is Rapid Automatized Naming (Ran)?mentioning
confidence: 83%
“…Some part of this stability can be explained by genetic sources, as a strong genetic influence has been shown in RAN performance (e.g., Byrne et al, 2006;Christopher et al, 2015;Davis et al, 2001;Petrill, Deater-Deckard, Thompson, DeThorne, & Schatschneider, 2006;Petrill et al, 2010;Samuelsson et al, 2007). There is also recent research evidence for specific genes that have been associated with RAN performance (Naples, Chang, Katz, & Grigorenko, 2009), some of them the same as those previously associated with dyslexia (Rubenstein, Raskind, Berninger, Matsushita, & Wijsman, 2014). In addition, brain imaging studies have recently shed further light on the neural basis of RAN performance, showing that activation during naming tasks is present in the areas involved in attention, and that eye-movement control is also present in the areas usually associated with reading tasks (McCrory, Mechelli, Frith, & Price, 2005;Misra, Katzir, Wolf, & Poldrack, 2004).…”
Section: What Is Rapid Automatized Naming (Ran)?mentioning
confidence: 83%
“…For Rapid Automatic Letter Naming RAN (test-retest reliability .90) (Wolf & Denckla, 2005), which is a measure of phonological loop for cross-code integration in language learning (Baddeley et al 1998) and has a genetic basis (Rubenstein, Raskind, Berninger, Matsushita, & Wijsman, 2014), the task is to name lower case printed letters arranged in rows; the. The total score is the time required to name all the letters in all the rows.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, the variations in functional connectivity observed during middle childhood and early adolescence may be due to genetic variants associated with spelling (e.g., Roeske et al, 2009; Rubenstein et al, 2011; Schulte-Kőrne et al, 1998) or endophenotypes for attention supporting language learning (e. g,, Posner and Rothbart, 2007; Rubenstein et al, 2014). On the other hand, the persisting problems may be due to instruction that is not tailored to the changing nature and requirements of the curriculum during middle childhood and adolescence (e.g., see Troia, 2009), which needs to include spelling and go beyond phonology only to orthography and morphology and their interrelationships with each other.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, prior research demonstrated a genetic basis for some of the working memory predictors: nonword repetition for phonological coding (Wijsman et al, 2000), phonological loop (Rubenstein, Raskind, Berninger, Matsushita, Wijsman, 2014), and switching attention (Rubenstein et al, 2014). For this study of adolescents and young adults with multigenerational family history of dyslexia, however, the focus was on the phenotypes—the behavioral expression—rather than genetic variations—and the potential heterogeneity and developmental change of the phenotypes.…”
Section: Specific Research Aim and Four Research Questionsmentioning
confidence: 96%